The Concept Of Hindu Cosmology In The Tattwa Jnana Text - Made Widya Sena, I Gusti (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2019)
The truth in daily life is certainly a wholeness in implementing the tattwa, ethics and acara of Hinduism as tri basic framework of Hinduism in Bali. This is because until now the implementation of the teaching trilogy is still running and standing alone in an incomplete and comprehensive manner. Sometimes it is found in the field of implementation of acaras and ethics are not equipped with tattwa philosophy in it. So that the knowledge of the people will be more rooted and rely on the basic concept indeed. This of course will increasingly corner the minds of the people about the doctrine that is not fundamental.One of the truths of tattwa written in the Vedic Scriptures is the concept of cosmology or the creation of the universe. Cosmology is one of the important knowledge in Hinduism, because cosmology not only provides knowledge about the creation of the universe, furthermore cosmology can explain the true nature of human beings, which so far is still very difficult to obtain. In Bali, this cosmological teaching is implied in local theology. Local theology that lived and developed in Bali until now is imbued with the teachings of the Vedic scriptures. Especially Siwaistic texts that always put forward the teachings of knowledge about the reality of God, the way to reach Him and the creation of the universe, both great bhuana agung and bhuana alit.